The Professional Development of School Principals: Insight from Indonesia - Mariyanah, Siti; Jamil, Riad; Arifin, Furqon; Barlian, Ujang Cepi (International Journal of Social and Management Studies, 2021)
The achievement of educational goals is very dependent on the leadership skills and wisdom of the principal who is one of the educational leaders. Therefore, this study examines how to become a professional school principal. The aims of this study are: (1) To find out how the professionalism of the principal's leadership depicts, (2) To find out how the tasks carried out by the principal, (3) To understand the role of the principal, (4) To find out the problems faced in realize the professionalism of the principal, (5) To know and understand the solution efforts in realizing the increase in the professionalism of the principal. The method of this study is observation, interviews and literature studies on the practice of principals' leadership in Indonesia. This study concludes that the principal is a formal leader who cannot be filled by people without being based on certain considerations. Therefore, the principal is responsible for carrying out leadership functions, both related to achieving educational goals and in creating a conducive school climate, which fosters the spirit of educators and students. Detailed discussion and suggestions are given at the end of this study.